Circulating tumor DNA analysis as a real-time method for monitoring tumor burden in melanoma patients undergoing treatment with immune checkpoint blockade. Issue 1 (16th December 2014) - Lipson, Evan J; Velculescu, Victor E; Pritchard, Theresa S; Sausen, Mark; Pardoll, Drew M; Topalian, Suzanne L; Diaz, Luis A
Abstract : Background: Assessment of therapeutic activity of drugs blocking immune checkpoints such as CTLA-4 and PD-1/PD-L1 can be challenging, as tumors may seem to enlarge or appear anew before regressing, due to intratumoral inflammation. We assessed whether circulating tumor DNA (ctDNA) levels could serve as an early indicator of true changes in tumor burden in patients undergoing treatment with these agents. Findings: Tumors from 12 patients with metastatic melanoma undergoing treatment with checkpoint blocking drugs were analyzed for the presence of hotspot somatic mutations in BRAF, cKIT, NRAS, and TERT . Plasma was collected serially from each patient and levels of ctDNA were compared with radiologic and clinical outcomes. In 5 of 10 patients studied, mutations were detected in BRAF (1), NRAS (2), TERT (1) and ALK (1). Analysis of plasma from 4 of 5 patients identified mutations identical to those found in tumor specimens. Plasma ctDNA levels ranged from undetectable (<0.01%) to 5.5% of total circulating cell-free DNA. In 3 patients, increasing ctDNA levels correlated with progressive disease assessed by radiography. In one patient, ctDNA levels increased after undergoing a needle biopsy of a tumor deposit. In another patient, ctDNA levels increased initially as lymphadenopathy progressed by examination, but then became undetectable 3 weeks prior to clinical improvement. Conclusions: Levels of ctDNA correlated with clinical and radiologic outcomes, and, in one case, preceded eventual tumor regression. Further prospective analysis is required to assess the utility of ctDNA as an early biomarker of clinical outcomes in patients receiving immune checkpoint blocking drugs.